Rethinking the concept of market orientation in the Portuguese non-profit sector:An exploratory study - Pinho, José Carlos M. (2001)
In the context of an increasing competitive environment, in which organisations are compelled to manage their resources and capabilities in a more efficient and effective way, the concept of marketing orientation has been acknowledged as highly important in the marketing and management literature. However, the existing literature is mainly focused on the for-profit sector, and to our best knowledge little research has been undertaken in the context of non-profit organisations. The purpose of this exploratory study is to test a measure of marketing orientation already used in previous studies and to assess its psychometric properties in the particular context of a Portuguese sample of nonprofit organisations.